Stem Cell Therapy—New Approach and Effective Treatment for Psoriasis - Hassan Ahmed, Hanan; J. Saadh, Mohamed; Abdul Kareem, Radhwan; Ballal, Suhas; Sharma, Shilpa; Guntaj, J.; Prasad, G. V. Siva; Mohammed Taher, Waam; Alwan, Mariem; Jasem Jawad, Mahmood; Khdyair Hamad, Atheer (Dermatology Practical & Conceptual, 2025)
The underlying mechanisms behind the development of psoriasis have become better understood in recent years. Key factors involved include the heightened reactivity of certain T-cell subsets (Th1 and Th17 cells), as well as dysregulation of regulatory T-cell (T-reg) function. Additionally, the complex interplay between immune cells, skin cells (keratinocytes), and the blood vessel endothelium has been shown to play an important role in the pathogenesis of psoriasis. Investigations have uncovered the impact that epidermal stem cells and their interactions with T cells have in psoriasis. Importantly, malfunctions across diverse stem cell types may constitute a central mechanism underlying the dysregulated inflammatory processes that characterize this condition. Nonetheless, a more thorough investigation of these mechanisms could present an opportunity to devise novel therapeutic approaches. In this publication, we reviewed the evidence regarding the role played by stem cells in the pathogenesis of psoriasis, as well as initial attempts at leveraging stem cells as a treatment modality.